(untitled) (Studia Prawnicze / The Legal Studies, 1984)
Building operations are usually carried out on the basis of documents of projects worked out by a designer as a result of a contract concluded with the orderer; the contractor receives documents of projects from the orderer. In practice documents often happen to be defective and the defects in projects for which the designer is responsible may cause defects in building works. Then a complex problem arises, namely the liability for defects of the object caused by defects in documents of projects. This problem has been solved in various ways so far. Joint liability of the contractor and designer by way of a guarantee for defects of object has been assumed. In arbitration practice the principle was been applied 11 recent years that the designer is liable on general principles of contractual liability (Art. 471 and the following of the Civil Code) for damage resulting from defects in building works caused by defects in documents of projects if the contractor proves that premises provided for by the provisions occur, on the basis of which he can be released from the liability in relation to the orderer by way of a guarantee for defects of object caused by defects in working plans. The author states that divergencies and controversies as to the character and Scope of liability for defects of building works caused by defects of projects result, on the one hand, from the system of cooperation between designers and building firms, and on the other hand, from lack of adequate, clear, and complex legal regulation in this field. Legal regulations should be changed so that a guarantee of the designer for defects in investment objects caused by defects in projects be stressed. Such liability would assume a form of compensative liability of a guarantee type.